Re-engineering Artificial Neoplastic Milieus: Taking Lessons from Mechano- and Topobiology - Leal-Egaña, Aldo; Balland, Martial; Boccaccini, Aldo R. (Trends in Biotechnology, 2019)
Traditionally, cancer-like scaffolds have been developed with tissue regeneration in mind and therefore designed to mimic the regenerative environment of otherwise healthy tissues. However, the tumoral niche exhibits specific biophysical cues far from being ‘cell friendly’, suggesting that a different approach should be taken to design these artificial neoplastic niches. From bare 2D surfaces to 3D and 1D microstructured platforms, this opinion article focuses on evolving approaches used to mimic in vitro the neoplastic niche, discussing why this pathology cannot be assessed with tissue engineering (TE) approaches (i.e., using scaffolds facilitating cell growth, migration, and matrix degradation in the absence of diffusional restrictions, among others), and suggests how to improve them with recent lessons learned from mechanobiology and topobiology.
CRIS-Team Scopus Importer:2019-10-15
Keywords: artificial neoplastic architecture; biomaterials for cancer research; cancer-like scaffolds; mechanobiology; topobiology; tumor-like scaffold